The economic effects of geoeconomic fragmentation - Anni Norring (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
First signs of headwinds to the global economy from geoeconomic fragmentation are emerging. This paper takes an overview on what is the current understanding of the economic effects of geoeconomic fragmentation. The estimated and modelled economic effects of geoeconomic fragmentation and geopolitics vary substantially. We need more research, standardized measures of geopolitical uncertainty, detailed data on protectionist measures and global value networks, plausible scenarios rooted in stylized facts and realistic models anchored in theory.
urn:nbn:fi-fe2024101179855
Keywords: 330; geoeconomic fragmentation; globalization; trade; technology diffusion